PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN CANDI MUARA JAMBI BERBASIS SEJARAH LOKAL PADA MATA KULIAH SEJARAH INDONESIA HINGGA ABAD 15 PROGRAM STUDI PENDIDIKAN SEJARAH UNIVERSITAS BATANGHARI JAMBI - Agustiningsih, Nur; Pamungkas, Satriyo (Universitas Batanghari Jambi, 2018)
The purpose of this research is to determine (1) the process of developing Muara Jambi Temple learning video based on local history in Indonesian history up to the 15th century subject History Study Program of Batanghari University Jambi (2) the advisability of Muara Jambi Temple learning video based on local history in Indonesian history up to the 15th century subject History Study Program of Batanghari University Jambi. The type of this research are research and development. This research emphasizes an effort to produce certain products that will be used in certain fields of science and can also be used in an activity that needs it. The development which was carried out in this research is developing video learning media. To determine the feasibility of the media, the media experts and material experts validated the media that had been made and then conducted a media trial to the students, the trial was carried out in three stages, one to one, small group trials, and field test trials. The results showed that (1) the stages of developing Muara Jambi Temple learning video based on local history in Indonesian history up to the 15th century subject adopted the steps or stages which were developed by Lee and Owens which consisted of five stages, namely analysis, design, development, implementation, and evaluation. (2) The results of the assessment by media experts for all aspects obtained an average score of 4.1 with good category and reasonable to be used. Furthermore, based on the media expert's assessment, the average of all aspects is 4.3 with a very good category so that the material reasonable to be used. The feasibility of Muara Jambi Temple learning video based on local history in Indonesian history up to the 15th century subject based on student assessment in the field test obtained an average of all aspects, namely 4.3 in the very good category so that the media was very suitable to be used in this learning activity.Keywords: Instructional Media, Local History, Muara Jambi Temple